Government e-strategic planning and management : practices, patterns and roadmaps - Anthopoulos, Leonidas G.; Reddick, Christopher G. (New York : Springer, 2014)
Various e-strategies have been developed since the late'90s in an attempt to describe the governmental vision for administrative and for societal change, the objectives and priorities with regard to the development of the Information and Communication Technologies (ICT) at national and at supranational levels. Terms such as the European Information Society, the U.S. Information Highways and the Korean and Chinese Informatization try to describe social transformation that occurs due to the ICT, and to determine means with which governments will capitalize the ICT to improve social life and to support economic growth. This book focuses on the context of managing Government e-Strategies. In this order it combines strategic management issues with recent trends in forming, planning and developing Government ICT strategies. It aims to identify various e-strategic management approaches that are followed worldwide, addresses the gaps that appear between e-strategic updates, and presents alternative strategic management methods adopted or uses strategic management methods as a means to describe the e-strategic evolution in different geographic regions. In this order, this book illustrates experiences from various national and supranational cases and offers the opportunity to readers to identify and compare the association between policies and ICT. Empirical findings from the United Arab Emirates (UAE) introduce readers to the context of this book, while part A collects chapters that address general strategic management issues in the ICT domain, such as evaluation, social involvements assessment, location information strategies, strategic documents analysis, effectiveness enhancement and innovation strategic management. On the other hand, part B presents various supranational, national and regional e-strategic cases and respective ICT management issues, beginning from Canada, continuing in Europe and more specifically in U.K., Spain and southern Europe; then Asian cases follow, concerning Turkey, Bangladesh, Hong Kong and Malaysia; finally, two African e-strategic cases are presented regarding Morocco and Zambia. Readers will gain significant outcomes and they will explore various e-strategic management issues such as evaluation, transformation, forming and planning, accompanied by methods for e-strategic analysis. It is of significant interest to scholars and policy-makers in public administration, management and information technology domains.
General Issues in Government e-Strategic Management -- International Cases.
Includes index.
Keywords: Public administration -- Technological innovations; Internet in public administration; Electronic government information